The impact of design factors of virtual and augmented reality on tertiary students’ user experience in Metaverse - Julius G. Garcia; Alvie Simonette Q. Alip (Institute of Advanced Engineering and Science, 2026)
The Metaverse is a convergent space integrating virtual reality (VR) and augmented reality (AR) technologies, with market projections rising from 65.5 billion in 2022 to 1.3 trillion by 2030. Despite rapid adoption in education, the specific contributions of visual elements, environmental design, and communication features to user experience (UX) remain underexplored, limiting evidence-based design and resource allocation. This study examined how these design factors in VR and AR environments influence UX in Metaverse platforms. Using a correlational research design, data were collected from 321 purposively sampled tertiary students from engineering and computer science departments across four higher education institutions, all familiar with Metaverse platforms. A structured questionnaire with validated 5-point Likert scales measured UX; visual elements (field of view, resolution, color, complexity, and style); environmental design (interactivity, cohesiveness, naturalness, and complexity); and communication features (text/audio/video tools, avatar interaction, and spatial audio). Multiple regression analysis assessed the independent and combined effects of these factors on UX. Results show that environmental design (β=0.424, p<0.001) and visual elements (β=0.298, p<0.001) are the primary predictors of UX, jointly explaining 47.3% of its variance, with a strong correlation between them (r=0.792). Communication features did not significantly influence UX (β=0.053, p=0.196), challenging assumptions about virtual connectedness and indicating that communication design should better support social interaction. These findings highlight the importance of well-designed, interactive virtual spaces and suggest that developers and educational institutions prioritize environmental design to advance immersive learning and broader Metaverse applications.